The corpus callosum and creativity revisited - Brown, Warren S.; Paul, Lynn K. (Frontiers in Human Neuroscience, 2024)
In 1969 Joseph Bogen, a colleague of Roger Sperry and the neurosurgeon who performed commissurotomies on Sperry's "split-brain" study participants, wrote an article subtitled "The Corpus Callosum and Creativity." The article (Bogen and Bogen, 1969) argued for the critical role of the corpus callosum and hemispheric specialization in creativity. Building on a four-stage model of creativity (learning, incubation, illumination, refinement) and Sperry's innovative studies, the Bogens posited that in the intact brain, creativity relies on two opposing functions of the corpus callosum: a) interhemispheric inhibition to facilitate simultaneous and independent activity of uniquely-specialized processing centers during learning and incubation and b) interhemispheric facilitation to support the increased bi-hemispheric integration and coordination which produces illumination. This article revisits the Bogens' theory considering scientific discoveries over the past 50 years. We begin by reviewing relevant findings from split-brain studies, and then briefly consider findings from studies that examine the association of creativity with callosal structure and function in neurotypical participants. Finally, we provide an in-depth discussion of creativity in persons with agenesis of the corpus callosum (ACC)-the congenital absence of the corpus callosum. These three lines of inquiry strongly support the theory suggested by Bogen and Bogen in 1969 and provide further clarification regarding the critical and unique role of the corpus callosum in creative cognition.